2020
DOI: 10.3390/cancers12082243
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Mapping Identifies Mutations in RYR2 and AHNAK as Associated with Favorable Outcome in Basal-Like Breast Tumors Expressing PD1/PD-L1

Abstract: Treatment with anti-PD-L1 antibodies has shown efficacy in basal-like breast cancer. In this context, identification of pre-activated immune tumors is a main goal. Here we explore mutations in PD1 and PD-L1 high-expressing tumors to identify genomic correlates associated with outcome. To do so, RNA-seq and mutation data from 971 breast cancer patients from the TCGA dataset were used to identify most prevalent mutations in patients with high levels of PD1 and PD-L1. Transcriptomic signatures associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…RYR2 is a major component of the intracellular Ca 2+ release channels and is associated with the endoplasmic or sarcoplasmic reticulum of several cell types, especially in cardiomyocytes (Lanner et al, 2010;Van Petegem, 2015). Recent studies demonstrated that RYR2 was significantly mutated in multiple cancers, and RYR2 was reported to be a driver gene in cervical cancer, colon cancer, breast cancer, head and neck cancer, and lung adenocarcinoma (Wolff et al, 2018;Schmitt et al, 2019;Wang et al, 2019;Cimas et al, 2020;Wei et al, 2020). Femi (2018) demonstrated that mutation in RYR2 was a prognosis biomarker of cervical cancer and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RYR2 is a major component of the intracellular Ca 2+ release channels and is associated with the endoplasmic or sarcoplasmic reticulum of several cell types, especially in cardiomyocytes (Lanner et al, 2010;Van Petegem, 2015). Recent studies demonstrated that RYR2 was significantly mutated in multiple cancers, and RYR2 was reported to be a driver gene in cervical cancer, colon cancer, breast cancer, head and neck cancer, and lung adenocarcinoma (Wolff et al, 2018;Schmitt et al, 2019;Wang et al, 2019;Cimas et al, 2020;Wei et al, 2020). Femi (2018) demonstrated that mutation in RYR2 was a prognosis biomarker of cervical cancer and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RYR2 is a major component of the intracellular Ca 2+ release channels and is associated with the endoplasmic or sarcoplasmic reticulum of several cell types, especially in cardiomyocytes [20,21]. Recent studies demonstrated that RYR2 was signi cantly mutated in multiple cancers, and RYR2 was reported to be a driver gene in cervical cancer, colon cancer, breast cancer, head and neck cancer, and lung adenocarcinoma [22][23][24][25][26]. Femi et al demonstrated that mutation in RYR2 was a prognosis biomarker of cervical cancer and breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…Femi et al demonstrated that mutation in RYR2 was a prognosis biomarker of cervical cancer and breast cancer [27]. Cimas et al found that mutation in RYR2 was associated with favorable outcome in basal-like breast tumors expressing PD-1/PD-L1 [22]. Wang et al reported that RYR2 mutation was a signi cant biomarker for suggesting high TMB in lung adenocarcinoma [26].…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of resistance to immune checkpoint blockade include the loss of β2-microglobulin, which impairs antigen presentation, and JAK1 or JAK2 mutations which make tumor cells insensitive to interferon gamma [113]. Recent studies have identified genomic correlates of response to immune checkpoint blockade which may help identify immunotherapy responsive tumors [114][115][116].…”
Section: Tumor Microenvironment and Immune Systemmentioning
confidence: 99%